Immunohistochemical study on the endocrine cells in the gastrointestinal tract of the ostrich - Tarakçi, Berrin Gençer; Yaman, Mine; Bayrakdar, Ali; Yaman, Ihsan (My University, 2008)
The study carried out an immunohistochemicai investigation on the regional distribution and relative frequency of endocrine cells in the gastrointestinal tract of the ostrich, (Struthio camelus camelus) using antibodies against serotonin, somatostatin-14, and vasoactive intestinal polypeptide (VIP), calcitonin gene related peptide (CGRP), neurotensin, cholecystokinin (CCK). Serotonin immunoreactive cells were observed in all regions of the gastrointestinal tract except the gizzard. They were particularly abundant in the duodenum and ileum, whereas the presence of somatostatin 14 positive cells was restricted to the proventricularis and gizzard. Substance P immunoreactive cells were predominant in the stomach. By contrast, VIP, CGRP, neurotensin and CCK immunoreactive cells were not detected in the ostrich.
Keywords: Calcitonin gene related peptide; Cholecystokinin; Immunohistochemistry; Neurotensin; Ostrich; Serotonin; Somatostatin-14; Substance P; Vasoactive intestinal polypeptide